Enhancing Internal Combustion Engine Performance with Textile Engineering Materials - Dr. Ganesh S. Kakad (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
The integration of textile engineering materials into internal combustion (IC) engines has the potential to revolutionize engine performance, efficiency, and longevity. This paper explores the utilization of advanced textile materials such as aramid fiber composites, ceramic-coated fabrics, and heat-resistant polymers in key engine components including pistons, cylinder heads, and gaskets. Through a series of experiments and analyses, this study evaluates the benefits of these materials in terms of thermal insulation, weight reduction, and vibration damping. Experimental results demonstrate significant improvements in thermal management and weight reduction, although challenges related to material compatibility and manufacturing complexity persist. The paper concludes that textile engineering offers promising advancements for IC engine technology and provides recommendations for future research.